Micro-electrode-dot-array digital microfluidic biochips : design automation, optimization, and test techniques /: design automation, optimization, and test techniques. ([2019]) - Lai, John Tsz Pang, 1975-; Chakrabarty, Krishnendu; Ho, Tsung-Yi; Lee, Chen-Yi
No abstract available